2022
DOI: 10.1177/09603271221078866
|View full text |Cite
|
Sign up to set email alerts
|

Oxymatrine attenuates TNBS-induced colinutis in rats through TLR9/Myd88/NF-κB signal pathway

Abstract: Objective: Due to its well-known anti-inflammatory property, oxymatrine (OMT) has received more attention on the aspect of treating ulcerative colitis. Although efforts have been undertaken to understand the therapeutic mechanism of OMT on ulcerative colitis (UC), the remedial principle is still ambiguous. Numerous studies have shown that TLR9/Myd88/NF-κB signal pathway played a key role in the pathogenesis of UC. Moreover, TLR9/Myd88/NF-κB signal pathway is a part of the most important pathways for regulating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…MPA showed an effective inhibition of hIMPDH2 with an inhibitory concentration (IC50) value of 28.79 ± 0.68 μm. Among these compounds, oxymatrine (purity >98%, purchased from Undersun Biologics, Xi'an), one of the major alkaloid components of Sophora roots (Li et al, 2022 ), showed the strongest inhibitory effect on hIMPDH2 with an IC 50 value of 4.10 ± 0.14 μm (Figure 7E ). These data suggested that oxymatrine is a novel inhibitor of hIMPDH2.…”
Section: Resultsmentioning
confidence: 99%
“…MPA showed an effective inhibition of hIMPDH2 with an inhibitory concentration (IC50) value of 28.79 ± 0.68 μm. Among these compounds, oxymatrine (purity >98%, purchased from Undersun Biologics, Xi'an), one of the major alkaloid components of Sophora roots (Li et al, 2022 ), showed the strongest inhibitory effect on hIMPDH2 with an IC 50 value of 4.10 ± 0.14 μm (Figure 7E ). These data suggested that oxymatrine is a novel inhibitor of hIMPDH2.…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [ 80 ] used oxymatrine, a quinolizidine alkaloid extracted from Sophora flavescens , to evaluate its mechanism in TNBS-induced colitis. After treatment, there was a reduction in IL-1β mRNA, TNF-α mRNA, and IL-6 mRNA, in addition to a reduction in NF-kB activation and decreases in toll-like receptor 9 (TLR9) and Myd88 expression in the TLR9/Myd88/NF-kB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…OMT effectively increased muribaculaceae, bifidobacterium abundance, lachnospiraceae, and ruminococcaceae, inhibited staphylococcaceae and bacteroides growth and regulated the intestinal flora structure in DSS-induced colitis [ 97 ]. OMT can inhibit PI3K/AKT and TLR9/MyD88/NF-κB signaling pathways and down-regulate pro-inflammatory cytokines such as IFN-γ, and MCP-1 to alleviate the disorder of gut microbiota caused by the decline of intestinal immune function caused by pro-inflammatory cytokines, thus alleviating the inflammatory damage of intestinal tissues [ 98 , 99 ]. OMT can protect the colonic mucosal barrier in DSS-induced colitis, inhibit inflammatory and oxidative responses and its mechanism is related to the RhoA/ROCK signaling pathway inhibiting the differentiation of Th17 cells and promoting the differentiation of Treg cells.…”
Section: Tcm Ingredients For the Uc Treatmentmentioning
confidence: 99%